The contrasting structure of Acts 12:5−17: A spatial reading - Van der Bergh, Ronald H. (HTS teologiese studies, 2013)
The episode of Peter’s rescue from prison in Acts 12:5–17 occupies an intriguing position in the narrative of Acts as a whole. Scholars hold differing views on the episode’s function. These views range from seeing the episode as a hermeneutical key to the work as a whole to making no discernable difference to the narrative whatsoever. The present article seeks to contribute to the debate by reading Acts 12:5–17 spatially. In paying attention to the various spatial references in the text, the movement of characters, their locales and their own and the reader’s experience of them being present or not present, a contrasting structure may be perceived in the text. Furthermore, spatiality helps to point out the contrast between different character groups in the narrative. Some implications for reading the episode in this contrasting fashion will be indicated, and the enigmatic statement about Peter’s ‘going to another place’ (Ac 12:17) will be read against the text’s spatial background.